2011
DOI: 10.5194/acp-11-12601-2011
|View full text |Cite
|
Sign up to set email alerts
|

Regional impacts of ultrafine particle emissions from the surface of the Great Lakes

Abstract: Abstract. Quantifying the impacts of aerosols on climate requires a detailed knowledge of both the anthropogenic and the natural contributions to the aerosol population. Recent work has suggested a previously unrecognized natural source of ultrafine particles resulting from breaking waves at the surface of large freshwater lakes. This work is the first modeling study to investigate the potential for this newly discovered source to affect the aerosol number concentrations on regional scales. Using the WRF-Chem … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Although a systematically varying salinity did not have a considerable effect on foam decay for oceanographically relevant salinities (say 30-40 g/kg), even low-salt concentrations drastically enhance the foaming characteristics of freshwater. This result raises concern on the use of saltwater models to predict bubble-mediated air-water interactions in freshwater bodies (see, e.g., Chung et al, 2011) .…”
Section: Discussionmentioning
confidence: 99%
“…Although a systematically varying salinity did not have a considerable effect on foam decay for oceanographically relevant salinities (say 30-40 g/kg), even low-salt concentrations drastically enhance the foaming characteristics of freshwater. This result raises concern on the use of saltwater models to predict bubble-mediated air-water interactions in freshwater bodies (see, e.g., Chung et al, 2011) .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that these particles were emitted due to wind-driven processes at the lake surface, a phenomenon that had not been previously reported. The potential impacts of this newly discovered source were later evaluated by Chung et al (2011), who found that the mechanism could enhance particle number concentrations by 20% in the remote northern Great Lakes region and 5% over other parts of the Great Lakes.…”
Section: Introductionmentioning
confidence: 99%
“…SSA contributes to both direct and indirect radiative forcing on a global scale (Lohmann and Feichter, 2005;Murphy et al, 1998). Aerosol generation from freshwater sources, such as the Laurentian Great Lakes, has been far less studied, with only a single ambient measurement (Slade et al, 2010) and modeling study (Chung et al, 2011) having examined the process to our knowledge. Slade et al (2010) observed the production of ultrafine (< 40 nm) aerosol, which increased in concentration as a function of wind speed, during periods of white-capped waves over Lake Michigan.…”
Section: Introductionmentioning
confidence: 99%
“…Through regional modeling, Chung et al (2011) found that these particles could increase surface level aerosol number concentrations, by ∼ 20 % over the remote northern Great Lakes and by ∼ 5 % over other parts of the Great Lakes, potentially affecting cloud nuclei (CCN) and/or ice nuclei (IN) concentrations over the Great Lakes region. Recently, aerosols produced from freshwater (a river) were demonstrated to have enhanced ability to act as IN, in comparison with SSA (Moffett, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation